Autonomous balance is a factor of changes in the components of the body composition of football players - D. V. Golubev (National Electronic Information Consortium (NEICON), 2022)
Objective: To investigate the nature of the relationship between the indicators of heart rate variability (HRV), reflecting the state of autonomous balance and the parameters of the component composition of the body of football players.Materials and methods: We studied n = 80 football players living in the northwestern region of the Russian Federation. Group data: 16.9 ± 0.8 years; weight 73.1 ± 4.7 kg; height 181.1 ± 4.9 cm. Monitoring of heart rate variability was carried out by the hardware and software complex "Omega-Sport, St.Petersburg". The bioelectric activity of the heart was recorded in the II standard lead from the sitting position in the morning (9:00-10:00). The assessment of the body composition of football players was carried out four times (January, April, August, November) using the Inbody 770 analyzer, Japan.Results: SI has a strong direct correlation with the indicators: "total fat content" (r = 0.994, P = 0.011); "total water content" (r = 0.811, P = 0.013). A direct strong correlation was established between SDNN and "total fat content" (r = 0.933, P = 0.009) and an inverse strong correlation with "total muscle mass" (r = -0.877, P = 0.006). pNN50 has a strong direct correlation with "total fat content" (r = 0.889, P = 0.011), in addition, there is a strong inverse correlation with "total muscle mass" (r = 0.767, P = 0.012). HF and "total fat content" (r = 0.733, P = 0.008) have a strong direct correlation; and with the indicator "total water content" of skeletal muscle mass (r = -0.874, P = 0.011) a strong inverse. A strong inverse relationship is shown between LF and "total fat content" (r = -0.766, P = 0.011), as well as a strong direct correlation with "total muscle mass" (r = 0.951, P = 0.013), "total water content" (r = 0.917, P = 0.008).Conclusions: There is a close correlation of the indicators "total muscle mass", "total fat content", "total water content" with a limited number of HRV parameters: SI, SDNN, pNN50, HF, LF. The study showed a significant (p < 0.05) predominance of: the activity of the parasympathetic ANS department - the competitive period, in which there was a significant (p < 0.05) increase in "total muscle mass", a decrease in "total fat content" in the 1st, 2nd and 3rd diagnostics; the activity of the sympathetic ANS department - the recovery period, which significantly (p < 0.05) affected: a decrease in "total muscle mass", "total water content"; an increase in "total fat content" in the 4th diagnosis.